Analysis of Pricing Strategies in The Internet Service Provider Business To Increase Company Sales (Case Study: PT. Indonesia Comnets Plus (ICON+) - Dermala Sari, Susilawati; Abdullah, Muhamad Al Faruq (International Journal of Advanced Multidisciplinary, 2024)
The internet has become component important in life every day in today's digital era. Online communication, shopping, reading news, watching movies and more Lots activity daily other, with rapidly development technology influences a number of aspect life we are increasing depend on the internet. Therefore? it, has available internet access reliable and fast very important for support need both at home, office, and more place others. So , the existence of an Internet Service Provider (ISP) is very important important. Life has experience a number of quite a change big as consequence from the existence of competing Internet Service Providers in build infrastructure so that it can sell service his to consumer. Internet access at any time This is "primary" needs for a number of group public certain so his presence No Can separated. One of Internet Service Provider company that serves consumer namely PT. Indonesia Comnets Plus. Research objectives This For discuss influencing factors? decision purchase to Internet Service Provider services with consumer product Iconnet from PT. Indonesia Comnets Plus. Where is the independent variable that influences it is Brand Image, service quality, and price are the ones factor consideration decision purchase to service Internet Service Provider.